2017
DOI: 10.1590/0034-737x201764040004
|View full text |Cite
|
Sign up to set email alerts
|

Action of ethylene on postharvest of summer squash ‘Menina Brasileira’

Abstract: RESUMOThe purpose of this study was to evaluate the sensitivity and the physiological responses of summer squash 'Menina Brasileira' to ethylene. Immature fruits were harvested and placed in 20 L sealed buckets, in which ethylene was applied at concentrations of 0.1, 1.0, 10, 100, and 1000 µL L -1 for 24 h. Fruits were placed in buckets with no ethylene as a control treatment. Thereafter, the fruits were taken out of the buckets and maintained on bench, wherein on days 0, 2, 4, 6, and 8, they were evaluated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In the fruits of summer squash the PMF increased with time of storage, regardless the application of ethylene (Araújo et al, 2017). This was also observed in 'Uba' mango (Silva et al, 2012).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In the fruits of summer squash the PMF increased with time of storage, regardless the application of ethylene (Araújo et al, 2017). This was also observed in 'Uba' mango (Silva et al, 2012).…”
Section: Resultssupporting
confidence: 59%
“…During the storage period, control fruits and those treated with 0.1 µL L -1 had an increase in the NRS and TSS contents, respectively. In the summer squash, the application of 10 μL L -1 got to a greater reduction in sugars than the highest doses, with a reduction of 22 and 35 % for total soluble sugars and reducing sugars, respectively (Araújo et al, 2017).…”
Section: /9mentioning
confidence: 90%
See 1 more Smart Citation
“…In that case, ethylene can be used to help characterizing the ripening metabolism (Archbold & Pomper, 2003). In climacteric fruit, external ethylene triggers its autocatalytic synthesis, anticipates the increase in respiration and accelerates quality changes, whereas in non-climacteric fruit, external ethylene leads to an imminent increase followed by a decrease in respiratory activity and has limited effect on quality changes (Abeles et al, 1992;Silva et al, 2009;Silva et al, 2012).Therefore, due to the lack of autocatalytic ethylene synthesis, non-climacteric fruit increase respiration rate and metabolic activity only during the exposure Bruna Silva Ribeiro et al to the hormone, decreasing thereafter (Abdi et al, 1998;Araújo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In climacteric fruits, during ripening, occurs a drastic increase in ethylene production, which results in high respiratory activity (Chitarra and Chitarra, 2005). Although some studies have shown that the 'Menina Brasileira' zucchini is considered non-climacteric, it has some sensitivity to ethylene (Araújo et al, 2017). Thus, it is also important to understand the sensitivity of ornamental minipumpkins to this phytohormone, by evaluating the ethylene production and respiration, in response to the application of compounds that inhibit the ethylene action, such as 1-methylcyclopropene (1-MCP).…”
Section: Introductionmentioning
confidence: 99%